2002
DOI: 10.1002/jmv.2148
|View full text |Cite
|
Sign up to set email alerts
|

Co‐delivery of GM‐CSF gene enhances the immune responses of hepatitis C viral core protein‐expressing DNA vaccine: Role of dendritic cells

Abstract: Hepatitis C virus (HCV) infection has become a critical public health problem worldwide. In Taiwan, it has been estimated that more than 300,000 people, 2% of the general population, have HCV infection. It has been well documented that direct delivery of gene intramuscularly can generate both humoral and cellular immunity, which more closely simulates the conditions of infection. In this study, female Balb/c mice immunized with HCV core plasmid DNA with or without adjuvant GM-CSF cytokine gene could induce bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Although the mechanism by which GM-CSF enhances immunity is not completely understood, evidence suggests that GM-CSF may work through its effects on APCs (16). In previous studies, when GM-CSF encoding plasmids were co-inoculated with antigen encoding plasmids, immunity was enhanced (12,23,31). These results fit the expectation to increase both cellular and humoral immune responses in our experiments.…”
Section: Discussionsupporting
confidence: 90%
“…Although the mechanism by which GM-CSF enhances immunity is not completely understood, evidence suggests that GM-CSF may work through its effects on APCs (16). In previous studies, when GM-CSF encoding plasmids were co-inoculated with antigen encoding plasmids, immunity was enhanced (12,23,31). These results fit the expectation to increase both cellular and humoral immune responses in our experiments.…”
Section: Discussionsupporting
confidence: 90%
“…Accumulating evidence, however, suggests that immune priming is initiated by professional APC rather than by these myocytes [8][9][10][11][12]. Since professional APC are not typically found in normal muscle tissue, they presumably migrate to the site of DNA inoculation in response to inflammatory or chemotactic signals [13][14][15]. Infiltrating APC may then either take up the plasmid DNA directly or cross-present expressed antigen to initiate immune responses [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, plasmid GM-CSF has received considerable attention given its ability to enhance DNA vaccine-elicited cellular immune responses specific for a variety of antigens [13][14][15]. We have previously reported that coadministration of plasmid GM-CSF with an HIV-1 Env DNA vaccine specifically augmented DNA vaccine-elicited CD4 + T lymphocyte responses but had minimal effects on CD8 + T lymphocyte or antibody responses [14].…”
Section: Introductionmentioning
confidence: 99%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF) is known to expand myeloid-derived dendritic cell (DC) populations (20,47), to augment antigeninduced humoral and cellular immune responses, and to affect the Th1/Th2 cytokine balance (45). It has been extensively used as an effective genetic and protein adjuvant to enhance immunogenicity of tumor and vaccine antigens (6,14,16,28,29,31,35,42,48,50,54,56). Another immunostimulatory molecule is CD40 ligand (CD40L), which is a surface molecule primarily expressed on mature CD4 ϩ T cells.…”
mentioning
confidence: 99%